Coherence Properties and Quantum Control of Silicon Vacancy Color Centers in Diamond. Issue 11 (28th September 2017) - Becker, Jonas Nils; Becher, Christoph
Abstract : Atomic‐scale impurity spins, also called color centers, in an otherwise spin‐free diamond host lattice have proven to be versatile tools for applications in solid‐state‐based quantum technologies ranging from quantum information processing (QIP) to quantum‐enhanced sensing and metrology. Due to its wide band gap, diamond can host hundreds of different color centers. However, their suitability for QIP or sensing applications has only been tested for a handful of these, with the nitrogen vacancy (NV) strongly dominating this field of research. Due to its limited optical properties, the success of the NV for QIP applications however strongly depends on the development of efficient photonic interfaces. In the past years the negatively charged silicon vacancy (SiV − ) center received significant attention due to its highly favourable spectral properties such as narrow zero phonon line transitions and weak phonon sidebands. Here, the recent work investigating the SiV center's orbital and electron spin coherence properties is reviewed as well as techniques to coherently control its quantum state using microwave as well as optical fields. Also, potential future experimental directions to improve the SiV's coherence time scale and to develop it into a valuable tool for QIP applications are outlined. Abstract : The silicon vacancy color center, an atom‐sized defect in diamond, has recently emerged as a promising tool for solid‐state‐based quantum technologies, due to its favorable optical properties. In this review, the authors summarize the center's electronic and optical properties, as well as recent advances in controlling its quantum state, making it accessible for future quantum information processing applications.